Zevinaella—a new barnacle genus (Scalpellomorpha: Arcoscalpellinae) associated with crinoids (Echinodermata) from the Caribbean - Shalaeva, Kate; Newman, William A. (Zootaxa, 2016)
A new genus, Zevinaella (Cirripedia: Scalpellomorpha: Scalpellidae: Arcoscalpellinae), is proposed to accommodate Trianguloscalpellum rodstromi (Boone, 1927) from Belize and Z. volentis gen. et sp. nov. from the Lesser Antilles, both occurring on crinoids. These two species are unique in lacking lower lateral plates (inframedian or second latera, L2s). We see no compelling evidence that the lack of L2s in Zevinaella is a consequence of fusion with the carinolatera (CLs), as appears to be the case in a near relative T. pentacrinarum, or of progressive reduction and potential loss, as in older specimens of Amigdoscalpellum spp. (Zevina, 1978b). However, this does not weaken the diagnosis of the new genus and, accordingly, the diagnoses for the family Scalpellidae Pilsbry, 1907 and the subfamily Arcoscalpellinae Zevina, 1978b are amended to accommodate the absence of the L2s.